Effect of Basic Fibroblast Growth Factor on Orthodontic Tooth Movement in Rats - Massoud Seifi (Cell Journal, 2013)
Objective: Basic fibroblast growth factor (bFGF) is a cytokine involved in angiogenesis, tissue remodeling and stimulation of osteoblasts and osteoclasts. The present study assesses the effects of a local injection of bFGF on the rate of orthodontic tooth movement.Materials and Methods: In this laboratory animal study, we randomly divided 50 rats into 5 groups of 10 rats each. Rats received 0.02 cc injections of the following doses of bFGF: group A (10 ng), group B (100 ng) and group C (1000 ng). Group D (positive control) received an orthodontic force and injection of 0.02 cc phosphate buffered saline whereas group E (negative control) received only the anesthetic drug. A nickel titanium spring was bonded to the right maxillary first molar and incisor. After 21 days, the rats were sacrificed and the distance between the first and second right molars was measured by a leaf gauge with 0.05 mm accuracy. ANOVA and Tukey’s HSD statistical tests were used for data analysis.Results: The greatest mean value of orthodontic tooth movement was 0.7700 mm observed in group C followed by 0.6633 mm in group B, 0.5333 mm in group A, 0.2550 mm in group D and 0.0217 mm in group E. There was a significantly higher rate of tooth movement in the test groups compared to the control groups (p<0.05). Among the test groups, the rate of tooth movement in group C was significantly higher than group A (p<0.05). Weight changes after the intervention were not significant when compared to the baseline values, with the exception of group E (p>0.05).Conclusion: The effect of bFGF on the rate of tooth movement was dose-dependent. Injection of 1000 ng bFGF in rats showed the most efficacy.